Characterization of the urogenital microbiome in Miniature Schnauzers with and without calcium oxalate urolithiasis. (7th July 2022) - Coffey, Emily L.; Gomez, Andres M.; Burton, Erin N.; Granick, Jennifer L.; Lulich, Jody P.; Furrow, Eva
Abstract: Background: Calcium oxalate (CaOx) uroliths are common in dogs. Humans with CaOx urolithiasis exhibit alterations of the urinary and urogenital microbiomes that might mediate urolith formation. Detection of urogenital microbes associated with CaOx in dogs could inform disease pathophysiology. Objective: To identify compositional differences in the urogenital microbiome of Miniature Schnauzers with and without CaOx uroliths. Animals: Nineteen midstream, voided urine samples from Miniature Schnauzers with (n = 9) and without (n = 10) a history of CaOx urolithiasis. Methods: Analytical cross‐sectional study. Microbial DNA was extracted from previously frozen urine samples and sequenced for the bacterial 16S rRNA V3‐V4 hypervariable regions. Diversity and composition of microbial populations were compared between urolith formers and controls. Results: Alpha and beta diversity measures were similar between groups. Five individual bacterial taxa differed in abundance (indicator values >0.5 and P < .05): Acinetobacter, 2 Geobacillus variants, and Hydrogenophaga were overrepresented in the urine of urolith formers, and Sphingopyxis was overrepresented in controls. Two distinct subtypes of urine microbial composition were observed based on beta diversity measures, independent of urolith status, and other clinical variables. Conclusions and Clinical Importance: Although we did not detect a difference in the overall urogenital microbial composition between groups, observed differences in individual bacterial taxa might be clinically relevant. For example, Acinetobacter was overrepresented in urolith formers and is associated with CaOx urolithiasis in humans. Two unique clusters of the microbiome were identified, independent of urolith status, which may represent distinct urotypes present in Miniature Schnauzers.